The CODA Model: A Review and Skeptical Extension of the Constructionist Model of Emotional Episodes Induced by Music - Lennie, Thomas M.; Eerola, Tuomas (Frontiers in Psychology, 2022)
This paper discusses contemporary advancements in the affective sciences (described together as skeptical theories) that can inform the music-emotion literature. Key concepts in these theories are outlined, highlighting their points of agreement and disagreement. This summary shows the importance of appraisal within the emotion process, provides a greater emphasis upon goal-directed accounts of (emotion) behaviour, and a need to move away from discrete emotion "folk" concepts and towards the study of an emotional episode and its components. Consequently, three contemporary music emotion theories (Juslin, 2019; Scherer and Coutinho, 2013; and Céspedes-Guevara, 2021) are examined through a skeptical lens. This critique highlights the over-reliance upon categorisation and a lack of acknowledgement of appraisal processes, specifically goal-directed appraisal, in examining how individual experiences of music emerge in different contexts. Based on this critique of current music-emotion models, we present our skeptically informed CODA model - Constructivistly-Organised Dimensional-Appraisal model. This model addresses skeptical limitations of existing theories, reinstates the role of goal-directed appraisal as central to what makes music relevant and meaningful to an individual in different contexts and brings together different theoretical frameworks into a single model. From the development of the CODA model, several hypotheses are proposed and applied to musical contexts. These hypotheses address theoretical issues such as acknowledging individual and contextual differences in emotional intensity and valence, as well as differentiating between induced and perceived emotions, and utilitarian and aesthetic emotions. We conclude with a sections of recommendations for future research. Altogether, this theoretical critique and proposed model points towards a positive future direction for music-emotion science. One where researchers can take forward testable predictions about what makes music relevant and meaningful to an individual.